New approach in determination of moisture diffusivity for rough rice components in combined far-infrared drying by finite element method. Issue 13 (1st September 2020) - Nosrati, Mojtaba; Zare, Dariush; Singh, Chandra B.; Stroshine, Richard L.
Abstract: Rough rice was dried using several combinations of heated air drying and far-infrared radiation (FIR). The moisture diffusion coefficients were determined at various drying air temperatures ranging from 30 to 50 °C and FIR intensities ranging from zero to 2000 W m −2 . The effective moisture diffusion coefficients increased with drying air temperature and FIR intensities. The coefficients varied from 1.5170 × 10 −10 to 2.5201 × 10 −9 m s −2 . Moreover, based on Fick's law, the equation for moisture transfer by diffusion was used to model the single kernel drying rate. The finite element method (FEM) was used to simulate moisture movement within an individual rice kernel. A new numerical approach was developed to determine moisture diffusion coefficients of the three main components of recently harvested rough rice. These components were the starchy endosperm, the bran, and the husk. A Polynomial-Arrhenius type general equation was developed to correlate the moisture diffusion coefficients of the kernel components with drying parameters. Based on FEM results, the prediction of the rough rice moisture content during drying was highly accurate.